Locally applied vascular endothelial growth factor a increases the osteogenic healing capacity of human adipose-derived stem cells by promoting osteogenic and endothelial differentiation - Behr, Björn; Tang, Chad; Germann, Günter; Longaker, Michael T.; Quarto, Natalina (Stem cells, 2011)
Human adipose-derived stem cells (hASCs) are known for their capability to promote bone healing when applied to bone defects. For bone tissue regeneration, both sufficient angiogenesis and osteogenesis is desirable. Vascular endothelial growth factor A (VEGFA) has the potential to promote differentiation of common progenitor cells to both lineages. To test this hypothesis, the effects of VEGFA on hASCs during osteogenic differentiation were tested in vitro. In addition, hASCs were seeded in murine critical-sized calvarial defects locally treated with VEGFA. Our results suggest that VEGFA improves osteogenic differentiation in vitro as indicated by alkaline phosphatase activity, alizarin red staining, and quantitative real-time polymerase chain reaction analysis. Moreover, local application of VEGFA to hASCs significantly improved healing of critical-sized calvarial defects in vivo. This repair was accompanied by a striking enhancement of angiogenesis. Both paracrine and, to a lesser degree, cell-autonomous effects of VEGFA-treated hASCs were accountable for angiogenesis. These data were confirmed by using CD31−/CD45− mouse ASCsGFP+ cells. In summary, we demonstrated that VEGFA increased osteogenic differentiation of hASCS in vitro and in vivo, which was accompanied by an enhancement of angiogenesis. Additionally, we showed that during bone regeneration, the increase in angiogenesis of hASCs on treatment with VEGFA was attributable to both paracrine and cell-autonomous effects. Thus, locally applied VEGFA might prove to be a valuable growth factor that can mediate both osteogenesis and angiogenesis of multipotent hASCs in the context of bone regeneration.